Resolução de problemas de matemática da Olimpíada Brasileira de Matemática das Escolas Públicas sob a visão da metodologia de Polya - Batista, Ailton Cecílio (Universidade Federal de São Carlos, 2025)
The objective of this work is to use Pólya’s problem-solving methodology as a tool for teaching and learning geometry concepts in the classroom. The study was developed based on four exercises from the question bank of the Brazilian Mathematics Olympiad for Public Schools (OBMEP), addressing topics such as perimeter, area, and formation rules. In addition to analyzing Pólya’s methodology, a generalization of the worked-out problems was made, which constitutes one of the main objectives of the book How to Solve It. This entire process was conducted in alignment with the skills and competencies outlined by the National Common Curricular Base (BNCC).
Solving mathematical problems from the Brazilian Mathematics Olympiad for Public Schools from the perspective of Polya's methodology
Keywords: Geometria; Metodologia de resolução de problemas; Olimpíada Matemática; Geometry; Problem-solving methodology; Mathematical Olympiad; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM::METODOS E TECNICAS DE ENSINO